2018
DOI: 10.21276/obgyn.2018.5.1.8
|View full text |Cite
|
Sign up to set email alerts
|

Study of association of lateral implantation of placenta with development of preeclampsia and its outcome

Abstract: Background: Pre eclampsia (PE) is a life threatening multisystem disorder, unique to pregnancy, complicating approximately 28% of pregnancies in developed countries and approximately 5-8% in developing countries. It is the 2 nd most important cause of maternal mortality in the world. The search for an ideal predictive test for PE still remains a major challenge for obstetricians. Objectives: To study whether ultrasonologically identified placental laterality can be used as a predictor of pre eclampsia. To asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
1
2
0
Order By: Relevance
“…This study is consistent with the study conducted by Kakkar et al, who concluded that 66.6% women with lateral placenta and 36.3% with central placenta developed preeclampsia. 17 Similar results were depicted from study concluded by Sandhya et al, Ambastha et al 18,19 It was demonstrated in our study that out of 83 women who developed preeclampsia, 22 women developed severe preeclampsia. Out of those 22 women, 19 (86.36%) had lateral placenta and three (13.64%) had central placenta.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This study is consistent with the study conducted by Kakkar et al, who concluded that 66.6% women with lateral placenta and 36.3% with central placenta developed preeclampsia. 17 Similar results were depicted from study concluded by Sandhya et al, Ambastha et al 18,19 It was demonstrated in our study that out of 83 women who developed preeclampsia, 22 women developed severe preeclampsia. Out of those 22 women, 19 (86.36%) had lateral placenta and three (13.64%) had central placenta.…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, it was observed that all the complications (preterm labour, eclampsia, HELLP syndrome, IUGR babies, transfer to RICU/ ICU were higher in women with lateral placenta but only eclampsia and IUGR were statistically significant (p value 0.008 and 0.014 respectively). 19,24 In women with lateral placenta, 4.8% developed renal failure and 3.6% women transferred to RICU/ICU. In contrast to this, no women with central placenta developed renal failure and transferred to RICU/ICU.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous branches from each of the two uterine arteries nourish the respective side of the uterus [ 4 ]. Both uterine arteries in patients with centrally placed placentas show comparable resistance, and the uteroplacental blood flow requirements are satisfied by equal distribution from both uterine arteries, which is absent when the placenta is laterally positioned [ 5 ].…”
Section: Introductionmentioning
confidence: 99%